Sediment deformation and production beneath soft-bedded Palaeozoic ice sheets - D.P. Le Heron (Department of Geodynamics and Sedimentology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); M. Heninger (Department of Geodynamics and Sedimentology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); C. Baal (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); M. Bestmann (GeoZentrum Nordbayern, Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU)) (Sedimentary Geology, 2020)
The abstract is available here: https://uscholar.univie.ac.at/o:2096916 The abstract is available here: https://uscholar.univie.ac.at/o:2096916